Understandings of wellbeing in the context of a living wage : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science, Massey University, Aotearoa New Zealand - Lorth, Christina (Massey University, 2021)
Academic, public, and media interest in the living wage (LW) is rising in Aotearoa/New Zealand (NZ) and globally. This is due, in part, to the growing inequalities and the need to find viable solutions to issues of income (in)adequacy and its impacts on wellbeing. This thesis addresses the lack of research into everyday wellbeing among low-income workers’ who have experiences of the LW in Aotearoa/NZ. A narrative approach informed by hermeneutic phenomenology and social practice theories were used to examine five case studies. Each case consisted of enhanced, semi-structured interviews (n=10 in total) and photo-elicitation projects that offered insights into participants’ experiences of wellbeing and the LW. This thesis documents how participants construct wellbeing as fundamentally relational, dynamic, and as a complex collection of multiple and interconnected dimensions. These manifest through everyday interactions with people, objects, practices, and places. The findings support the assertion that earning a LW has implications for participants’ wellbeing, increases civic and social participation and leisure activities, and enhances the overall quality of life. Key considerations also include work characteristics, relationships, material living conditions, and household composition. This research aligns with existing research and offers more holistic, nuanced, and context-specific understandings of wellness and the LW.
Keywords: wellbeing; living wage; decent work; relationality; participation; photo-elicitation; 520304 Health psychology